Comparative analysis of classical and stochastic Maccari system of nonlinear equations - Iqbal, Muhammad Sajid; İnç, Mustafa; Sohail, Saba; Raheem, Adil; Hussain, Shabbir; Mahmoud, Emad E. (Vilnius Univ, Inst Mathematics & Informatics, 2024)
In this paper, the exact solutions of classical and stochastic Maccari system is constructed. The exact comparative solutions are examined and plotted. Interesting results in the case of multiplicative noise are formulated and graphically elaborated. The applications of the stochastic Maccari system are added for the physical purpose. The existence of results for the real part of underlying system are discussed first time for a priori estimates. The perturbations, which disturbed the formation of Langmuir waves, are geometrically expressed in this article. Due to the presence of multiplicative noise term, our system brings a real flavor to the dynamics of the problem.
Keywords: stochastic partial differential equation; Langmuir soliton; MEDA method